Two new species of the genus Amemboides Polhemus & Andersen, 1984, stat. nov. (Hemiptera: Heteroptera: Gerromorpha: Gerridae) from Vietnam - Tran, A. D.; Polhemus, J. T. (Zootaxa, 2009)
Amemboides Polhemus & Andersen, 1984, stat. nov., is herein recognised as separate genus from Amemboa Esaki, 1925. This paper describes two new species of Amemboides from Vietnam: Amemboides falcatus and Amemboides gladiolus. Amemboides sexualis (Polhemus & Andersen, 1984) is recorded from Vietnam for the first time.